2008
DOI: 10.5993/ajhb.32.1.6
|View full text |Cite
|
Sign up to set email alerts
|

An Abstinence Program's Impact on Cognitive Mediators and Sexual Initiation

Abstract: Objectives:To evaluate the impact of an abstinence education program on sexual intercourse initiation and on possible cognitive mediators of sexual initiation for virgin seventh graders in suburban Virginia. Methods: Measures of sexual behavior and 6 mediating variables were compared at 3 time periods for program participants and a matched comparison group (n=550), controlling for pretest differences. Results: At posttest, program stu-dents scored significantly better on 4 of the 6 mediators. After one year, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…RA students were also less likely to engage in unprotected sex at last vaginal intercourse, either by using a condom or by abstaining from sex. These findings support evidence from previous studies that middle school programs emphasizing abstinence, [10,12,13] and more specifically abstinence-until-marriage, [9] can effectively delay sexual initiation among subsets of youth and may positively impact sexually experienced youth. [11] However, adverse effects among males and sexually experienced students are worrying and warrant further investigation to understand how males and sexually experienced youth process risk avoidance messages to better tailor activities to their needs.…”
Section: Discussionsupporting
confidence: 89%
“…RA students were also less likely to engage in unprotected sex at last vaginal intercourse, either by using a condom or by abstaining from sex. These findings support evidence from previous studies that middle school programs emphasizing abstinence, [10,12,13] and more specifically abstinence-until-marriage, [9] can effectively delay sexual initiation among subsets of youth and may positively impact sexually experienced youth. [11] However, adverse effects among males and sexually experienced students are worrying and warrant further investigation to understand how males and sexually experienced youth process risk avoidance messages to better tailor activities to their needs.…”
Section: Discussionsupporting
confidence: 89%
“…Abstinence education has been questioned as a public health strategy in recent years on the basis of inadequate evidence of effectiveness [29,30]. Recent studies showing positive effects of abstinence education programs have sought to fill this evidence gap [1,2]. However, the issue remains highly contentious and public policy makers have debated the future of U.S. government funding for Title V programs [3].…”
Section: Discussionmentioning
confidence: 99%
“…Since enactment of Title V, Section 510 of the Personal Responsibility and Work Opportunity Reconciliation Act of 1996, U.S. Government policy and the primary focus of related funding has been sexual abstinence education. Since 1998, the Title V, Section 510 program has received approximately $50 million annually to teach abstinence from sexual activity as the expected standard for children under age 18. There is ongoing debate about the effectiveness of abstinence education programs funded under Title V [1][2][3][4]. Some recent studies have found that students who received abstinence education had lower rates of sexual activity compared to youth who did not receive abstinence training [1,2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study with a one year follow up of an abstinence program's impact on sexual behavior found a reduction in sexual initiation. Virgin students in the experimental group were less likelyabout half as likely-to initiate sexual intercourse as the virgins in the comparison groups during the year following the intervention (Weed, Ericksen, Lewis, Grant, & Wibberly, 2008).…”
Section: Facts: Oregon Style Implementationmentioning
confidence: 90%